MUATAN TUGAS KENABIAN DALAM SASTRA MELAYU KLASIK: KAJIAN SASTRA PROFETIK - Rakhmat Soleh (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
This article contains a study about the content of prophetic tasks presented in classical Malay literary works, by taking several works from period to period. The prose works that will become the object of study include Hikayat Sri Rama, Hikayat Isma Yatim, Hikayat Iskandar Zulkarnain, and Hikayat Mareskalek. This study uses a prophetic literary approach initiated by Kuntowijoyo. Kuntowijoyo states that there are three prophetic literary tasks, namely amar ma'ruf (ordering kindness, humanization), nahi munkar (preventing evil, liberation), and tu' minunabillah (faith in transcendence). So, prophetic ethics contains three things, namely humanization, liberation, and transcendence, to serve all mankind, Rahmatalil Alamin. The results of the study show that these three things, humanization, liberation, and transcendence are contained in the sagas that are the object of this research, namely the Hikayat Sri Rama (representing the Hindu era), Hikayat Isma Yatim (Hindu-Parsi-Islam), Hikayat Iskandar Zulkarnain ( Hero of Islam), and Hikayat Mareskalek (Historical Literature, modern prose). Of these four saga, the saga of Mareskalek is the most complete in terms of humanization and liberation. The Mareskalek character, who in fact is Daendels, is given the burden to carry out professional tasks. Meanwhile, in the prophetic task that is dominant in nature found in the Hikayat Sri Rama, Hikayat Isma Yatim, and Hikayat Iskandar Zulkarnain, there is also a humanization and liberation content.